A technique avoiding cardioplegia delivery complications: a case using systemic hyperkalemia cardiopulmonary bypass combined with circulatory arrest - Takeichi Tomohisa; Morimoto Yoshihisa; Yamada Akitoshi; Tanaka Takanori (The Journal of ExtraCorporeal Technology)
We conducted a high-risk redo mitral valve replacement through a right mini-thoracotomy without rib spreading (redo-MICS MVR) under systemic hyperkalemia combined with circulatory arrest to circumvent complications associated with cardioplegia delivery. The patient, a 75-year-old man, had a predicted mortality rate of 20%. Initial antegrade cardioplegia successfully induced cardiac arrest, which was administered every 30 min. However, upon infusion of the second dose of cardioplegia, the aortic root pressure was approximately 20 mmHg. Despite multiple attempts to re-cross the clamp, the aortic root pressure did not improve. Consequently, retrograde cardioplegia was considered, but due to significant adhesion of the inferior vena cava, this approach was abandoned. Thus, the procedure was altered to utilize systemic hyperkalemia without aortic cross-clamping (ACC). Given the preoperative transesophageal echocardiography (TEE) diagnosis of mild aortic regurgitation, maintaining a clear surgical field was challenging, necessitating the combination of redo-MVR with circulatory arrest. This case exemplifies the successful management of cardioplegia delivery complications using systemic hyperkalemia and circulatory arrest, resulting in a favorable postoperative recovery for the patient.